Super-hydrophilic flame-retardant coating containing nano material and preparation method of super-hydrophilic flame-retardant coating

By using nanomaterials and specific chemical combinations in the coating, the problem of poor use of existing coatings in high temperature, acidic or alkaline environments is solved, achieving the versatility and wide applicability of the coating.

CN119463635APending Publication Date: 2025-02-18深圳粤源建设有限责任公司

Patent Information

Application Number
CN202411679145.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing coatings are not effective in high temperature, acidic or alkaline environments, and it is difficult to have various functions such as easy cleaning, flame retardant, and weather resistance.

Method used

Using a super hydrophilic flame retardant coating containing nanomaterials, grafting of amyotrophic nanosilica and triphenyl phosphate by modifying the combination of epoxy resin, polyethyleneimine, defoaming agent, solvent and water Modification to enhance the hydrophilicity, flame retardancy and weather resistance of the coating.

Benefits of technology

It achieves excellent properties of the coating in a variety of environments, including good hydrophilicity, heat resistance, acid resistance, alkali resistance and flame retardancy, and is suitable for a wide range of production and living environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147846240000071
    Figure BDA0005147846240000071
  • Figure BDA0005147846240000081
    Figure BDA0005147846240000081
Patent Text Reader

Abstract

The invention relates to the technical field of flame-retardant coatings, and discloses a nano-material-containing super-hydrophilic flame-retardant coating and a preparation method thereof, and the nano-material-containing super-hydrophilic flame-retardant coating comprises modified epoxy resin, polyethyleneimine, a defoaming agent, a solvent and water. The modified epoxy resin is grafted and modified by aminated nano silicon dioxide, pyridine groups, amino groups and triphenyl phosphate, the aminated nano silicon dioxide and the triphenyl phosphate can effectively improve the flame retardance, the pyridine groups can play a role in corrosion prevention, the shelf life is prolonged, and the hydrophilic property of the coating is greatly improved through multi-amination. The water-based flame-retardant coating has excellent hydrophilicity, heat resistance, acid resistance, alkali resistance and flame retardance, is suitable for most production and living environments, is simple and convenient in production process, and is convenient to widely popularize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant coatings, in particular to a super hydrophilic flame retardant coating containing nano materials and a preparation method thereof. Background Art

[0002] The surfaces of various objects in life are coated, which plays a role in beauty, easy cleaning, anti-corrosion, anti-rust and other functions. The functions and applications of coatings are particularly extensive. Different environments require different functional coatings. High temperature environments require high temperature resistance, acidic environments require acid resistance, and alkaline environments require alkali resistance. Therefore, there are various types of coatings. Wrong selection of coatings will lead to poor coating effects, damage to the coated objects, and economic losses. A multi-functional coating has been developed that is easy to clean, flame retardant, weather resistant, etc. It can be applied to a variety of working environments, greatly improving its application value. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the deficiencies in the prior art, the present invention provides a super hydrophilic flame retardant coating containing nanomaterials and a preparation method thereof.

[0005] (II) Technical solution

[0006] A super hydrophilic flame retardant coating containing nanomaterials, comprising the following weight components:

[0007] 10-30 parts of modified epoxy resin, 10-20 parts of polyethyleneimine, 1-3 parts of defoaming agent, 20-30 parts of solvent, 30-60 parts of water;

[0008] The preparation method of the super hydrophilic flame retardant coating is as follows:

[0009] S1. Mix ethanol and ammonia water, stir at 30-60°C for 1-2h, quickly add ethyl orthosilicate, stir overnight at 30-50°C, then add γ-aminopropyltriethoxysilane, stir for 3-6h, heat and reflux for 1-3h, centrifuge and filter, wash in anhydrous ethanol for 2-5 times, disperse in dichloromethane to obtain amino-modified nano-silica;

[0010] S2, mixing bisphenol A epoxy resin and pyridine carboxylic acid, stirring evenly, placing in an oil bath, stirring and reacting at 130-180° C. for 2-6 hours to obtain intermediate 1;

[0011] S3, mixing intermediate 1 and amino-modified nano-silica, stirring evenly, adding concentrated sulfuric acid as a catalyst, heating to reflux, reacting for 3 to 6 hours, to obtain intermediate 2;

[0012] S4, cool triethylenetriamine in an ice-water bath, pass nitrogen, slowly add intermediate 2 and methanol solution, react at 20-30°C for 2-5h, remove methanol under reduced pressure, raise the temperature to 130-160°C and continue to react under reduced pressure for 2-5h to obtain intermediate 3;

[0013] S5, mixing the intermediate 3 and triphenyl phosphate, stirring evenly at 60-80° C. to obtain a modified epoxy resin;

[0014] S6. Add modified epoxy resin and polyethyleneimine to the solvent in sequence, stir evenly, add the mixture into water and stir continuously for 10 to 30 minutes, add defoaming agent, stir evenly, seal and package to obtain a super hydrophilic flame retardant coating.

[0015] Preferably, in step S1, the mass ratio of ethanol, ammonia water, ethyl orthosilicate and γ-aminopropyltriethoxysilane is 100:5-10:5-10:0.5-2.

[0016] Preferably, in step S2, the mass ratio of bisphenol A epoxy resin to pyridine carboxylic acid is 1:0.4-0.6.

[0017] Preferably, in step S3, the mass ratio of the intermediate 1, the amino-modified nano-silicon dioxide, and the catalyst concentrated sulfuric acid is 1:0.1-0.5:0.05-0.1.

[0018] Preferably, in step S4, the mass ratio of triethylenetriamine, intermediate 2, and methanol solution is 1:1-1.5:2-3.

[0019] Preferably, in step S5, the mass ratio of intermediate 3 to triphenyl phosphate is 1:0.3-0.6.

[0020] Preferably, the defoaming agent is polydimethylsiloxane.

[0021] Preferably, the solvent is ethylene glycol, isopropanol or N,N-dimethylformamide.

[0022] Preferably, the super hydrophilic flame retardant coating is used in construction engineering, road engineering, water conservancy engineering, and medical industry.

[0023] Preferably, the preparation steps are as follows:

[0024] The surface of the object to be coated is roughened and cleaned, placed in a dust-free room, dried at 60-80°C for 10-30 minutes, and the super-hydrophilic flame-retardant coating is evenly sprayed. After the spraying is completed, it is dried at 50-80°C for 5-10 minutes, and dried at a temperature of 200-400°C for 30-60 minutes. The coating on the surface of the object is completed.

[0025] (III) Beneficial technical effects

[0026] A super hydrophilic flame retardant coating containing nano materials comprises: modified epoxy resin, polyethyleneimine, defoaming agent, solvent and water.

[0027] The modified epoxy resin is grafted and modified by amino nano-silica, pyridine group, amino group and triphenyl phosphate. Aminated nano-silica and triphenyl phosphate can effectively improve the flame retardancy, the pyridine group can play an anti-corrosion effect and extend the shelf life, and the polyamino group greatly improves the hydrophilicity of the coating. The invention has excellent hydrophilicity, heat resistance, acid resistance, alkali resistance and flame retardancy, is suitable for most production and living environments, has a simple production process, and is easy to promote widely. DETAILED DESCRIPTION

[0028] Example 1

[0029] S1. Mix 10 kg of ethanol and 0.5 kg of ammonia water, stir at 30 ° C for 1 hour, quickly add 0.5 kg of ethyl orthosilicate, stir at 30 ° C overnight, then add 0.05 kg of γ-aminopropyltriethoxysilane, stir for 3 hours, heat and reflux for 1 hour, centrifuge and filter, wash twice in anhydrous ethanol, disperse in 10 kg of dichloromethane to obtain amino-containing nano-silica.

[0030] S2. Mix 30 kg of bisphenol A epoxy resin and 12 kg of pyridine carboxylic acid, stir evenly, place in an oil bath, and stir and react at 130° C. for 2 h to obtain intermediate 1.

[0031] S3. Mix the intermediate 1 and the amino-modified nano-silica, stir evenly, add 3 kg of concentrated sulfuric acid as a catalyst, heat to reflux, and react for 3 hours to obtain the intermediate 2.

[0032] S4. Cool 50 kg of triethylenetriamine in an ice-water bath, pass nitrogen, slowly add intermediate 2 and 100 kg of methanol solution, react at 20°C for 2 h, remove methanol under reduced pressure, heat to 130°C and continue to react under reduced pressure for 2 h to obtain intermediate 3.

[0033] S5. Mix the intermediate 3 and 30 kg of triphenyl phosphate, and stir evenly at 60° C. to obtain a modified epoxy resin.

[0034] S6. Add 10 kg of modified epoxy resin and 10 kg of polyethyleneimine to 20 kg of solvent ethylene glycol in sequence and stir evenly. Add the mixture to 30 kg of water and stir continuously for 10 min. Add 1 kg of defoaming agent polydimethylsiloxane and stir evenly. Seal and package to obtain a super hydrophilic flame retardant coating.

[0035] Example 2

[0036] S1. Mix 10 kg of ethanol and 1 kg of ammonia water, stir at 60 ° C for 2 hours, quickly add 1 kg of ethyl orthosilicate, stir at 50 ° C overnight, then add 0.2 kg of γ-aminopropyltriethoxysilane, stir for 6 hours, heat and reflux for 3 hours, centrifuge and filter, wash 5 times in anhydrous ethanol, and disperse in 10 kg of dichloromethane to obtain amino-containing nano-silica.

[0037] S2. Mix 30 kg of bisphenol A epoxy resin and 18 kg of pyridine carboxylic acid, stir evenly, place in an oil bath, and stir and react at 180° C. for 6 h to obtain intermediate 1.

[0038] S3. Mix the intermediate 1 and the amino-modified nano-silica, stir evenly, add 3 kg of concentrated sulfuric acid as a catalyst, heat to reflux, and react for 6 hours to obtain the intermediate 2.

[0039] S4. Cool 60 kg of triethylenetriamine in an ice-water bath, pass nitrogen, slowly add intermediate 2 and 150 kg of methanol solution, react at 30 °C for 5 h, remove methanol under reduced pressure, raise the temperature to 160 °C and continue to react under reduced pressure for 5 h to obtain intermediate 3.

[0040] S5. Mix the intermediate 3 and 60 kg of triphenyl phosphate, and stir evenly at 80° C. to obtain a modified epoxy resin.

[0041] S6. Add 30 kg of modified epoxy resin and 20 kg of polyethyleneimine to 30 kg of solvent isopropanol in sequence and stir evenly. Add the mixture to 60 kg of water and stir continuously for 30 minutes. Add 3 kg of defoaming agent polydimethylsiloxane and stir evenly. Seal and package to obtain a super hydrophilic flame retardant coating.

[0042] Example 3

[0043] S1. Mix 10 kg of ethanol and 0.6 kg of ammonia water, stir at 40 ° C for 2 hours, quickly add 0.8 kg of ethyl orthosilicate, stir at 40 ° C overnight, then add 0.08 kg of γ-aminopropyltriethoxysilane, stir for 4 hours, heat and reflux for 2 hours, centrifuge and filter, wash 3 times in anhydrous ethanol, and disperse in 10 kg of dichloromethane to obtain amino-containing nano-silica.

[0044] S2. Mix 30 kg of bisphenol A epoxy resin and 15 kg of pyridine carboxylic acid, stir evenly, place in an oil bath, and stir and react at 140° C. for 3 h to obtain intermediate 1.

[0045] S3. Mix the intermediate 1 and the amino-modified nano-silica, stir evenly, add 3 kg of concentrated sulfuric acid as a catalyst, heat to reflux, and react for 5 hours to obtain the intermediate 2.

[0046] S4. Cool 52 kg of triethylenetriamine in an ice-water bath, pass nitrogen, slowly add intermediate 2 and 120 kg of methanol solution, react at 25 °C for 3 h, remove methanol under reduced pressure, heat to 140 °C and continue to react under reduced pressure for 3 h to obtain intermediate 3.

[0047] S5. Mix the intermediate 3 and 40 kg of triphenyl phosphate, and stir evenly at 65° C. to obtain a modified epoxy resin.

[0048] S6. Add 15 kg of modified epoxy resin and 12 kg of polyethyleneimine to 25 kg of solvent ethylene glycol and isopropanol in turn, stir evenly, add the mixture to 40 kg of water and stir continuously for 15 minutes, add 2 kg of defoaming agent polydimethylsiloxane, stir evenly, seal and package to obtain a super hydrophilic flame retardant coating.

[0049] Example 4

[0050] S1. Mix 10 kg of ethanol and 0.8 kg of ammonia water, stir at 50 ° C for 1 hour, quickly add 0.6 kg of ethyl orthosilicate, stir at 45 ° C overnight, then add 0.1 kg of γ-aminopropyltriethoxysilane, stir for 5 hours, heat and reflux for 3 hours, centrifuge and filter, wash 4 times in anhydrous ethanol, and disperse in 10 kg of dichloromethane to obtain amino-containing nano-silica.

[0051] S2. Mix 30 kg of bisphenol A epoxy resin and 16 kg of pyridine carboxylic acid, stir evenly, place in an oil bath, and stir and react at 140° C. for 5 h to obtain intermediate 1.

[0052] S3. Mix the intermediate 1 and the amino-modified nano-silica, stir evenly, add 3 kg of concentrated sulfuric acid as a catalyst, heat to reflux, and react for 5 hours to obtain the intermediate 2.

[0053] S4. Cool 55 kg of triethylenetriamine in an ice-water bath, pass nitrogen, slowly add intermediate 2 and 140 kg of methanol solution, react at 26 °C for 4 h, remove methanol under reduced pressure, raise the temperature to 150 °C and continue to react under reduced pressure for 4 h to obtain intermediate 3.

[0054] S5. Mix the intermediate 3 and 50 kg of triphenyl phosphate, and stir evenly at 70° C. to obtain a modified epoxy resin.

[0055] S6. Add 20 kg of modified epoxy resin and 18 kg of polyethyleneimine to 28 kg of solvent ethylene glycol in sequence and stir evenly. Add the mixture to 50 kg of water and stir continuously for 20 min. Add 1 kg of defoaming agent polydimethylsiloxane and stir evenly. Seal and package to obtain a super hydrophilic flame retardant coating.

[0056] Example 5

[0057] S1. Mix 10 kg of ethanol and 0.7 kg of ammonia water, stir at 55 ° C for 2 h, quickly add 0.9 kg of ethyl orthosilicate, stir at 40 ° C overnight, then add 0.15 kg of γ-aminopropyltriethoxysilane, stir for 5 h, heat and reflux for 1 h, centrifuge and filter, wash 4 times in anhydrous ethanol, disperse in 10 kg of dichloromethane to obtain amino-containing nano-silica.

[0058] S2. Mix 30 kg of bisphenol A epoxy resin and 16 kg of pyridine carboxylic acid, stir evenly, place in an oil bath, and stir to react at 160° C. for 4 h to obtain intermediate 1.

[0059] S3. Mix the intermediate 1 and the amino-modified nano-silica, stir evenly, add 3 kg of concentrated sulfuric acid as a catalyst, heat to reflux, and react for 5 hours to obtain the intermediate 2.

[0060] S4. Cool 55 kg of triethylenetriamine in an ice-water bath, pass nitrogen, slowly add intermediate 2 and 130 kg of methanol solution, react at 30 °C for 5 h, remove methanol under reduced pressure, raise the temperature to 150 °C and continue to react under reduced pressure for 2 h to obtain intermediate 3.

[0061] S5. Mix the intermediate 3 and 45 kg of triphenyl phosphate, and stir evenly at 80° C. to obtain a modified epoxy resin.

[0062] S6. Add 10 kg of modified epoxy resin and 20 kg of polyethyleneimine to 30 kg of solvent N,N-dimethylformamide in sequence, stir evenly, add the mixture to 30 kg of water and stir continuously for 10 minutes, add 2 kg of defoaming agent polydimethylsiloxane, stir evenly, seal and package to obtain a super hydrophilic flame retardant coating.

[0063] Comparative Example 1

[0064] 10 kg of epoxy resin and 20 kg of polyethyleneimine were added to 20 kg of ethylene glycol solvent in sequence, and the mixture was stirred evenly. 2 kg of defoaming agent polydimethylsiloxane was added, and the mixture was stirred evenly. The mixture was sealed and packaged to obtain a super hydrophilic flame retardant coating.

[0065] Performance Test:

[0066] The coatings of Examples 1 to 5 and Comparative Example 1 were sprayed on a stainless steel table by a spraying process and tested. The boiling water resistance test was based on the standard GB / T 5237.4-2008, the acid resistance test was based on the standard GB / T 5237.4-2008, and the alkali resistance test was based on the standard GB / T 9265-2009.

[0067] Table 1

[0068] Group Static contact angle Boiling water resistant Acid resistant Alkali resistance Example 1 4° No change No change No change Example 2 3° No change No change No change Example 3 5° No change No change No change Example 4 4° No change No change No change Example 5 3° No change No change No change Comparative Example 1 8° Shedding No change No change

[0069] It can be seen from Table 1 that Examples 1 to 5 have good superhydrophilic properties and good resistance to boiling water, acid and alkali.

[0070] Flame retardancy test: The coatings of Examples 1 to 5 and Comparative Example 1 were sprayed on a PMMA plate by a spraying process, and a flame retardancy test was performed using a cone calorimeter.

[0071] Table 2

[0072]

[0073]

[0074] It can be seen from Table 2 that Examples 1 to 5 have better flame retardancy.

[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A super hydrophilic flame retardant coating containing nanomaterials, characterized in that: Contains the following components by weight: 10-30 parts of modified epoxy resin, 10-20 parts of polyethyleneimine, 1-3 parts of defoaming agent, 20-30 parts of solvent, 30-60 parts of water; The preparation method of the super hydrophilic flame retardant coating is as follows: S1. Mix ethanol and ammonia water, stir at 30-60°C for 1-2h, quickly add ethyl orthosilicate, stir overnight at 30-50°C, then add γ-aminopropyltriethoxysilane, stir for 3-6h, heat and reflux for 1-3h, centrifuge and filter, wash in anhydrous ethanol for 2-5 times, disperse in dichloromethane to obtain amino-modified nano-silica; S2, mixing bisphenol A epoxy resin and pyridine carboxylic acid, stirring evenly, placing in an oil bath, stirring and reacting at 130-180° C. for 2-6 hours to obtain intermediate 1; S3, mixing intermediate 1 and amino-modified nano-silica, stirring evenly, adding concentrated sulfuric acid as a catalyst, heating to reflux, reacting for 3 to 6 hours, to obtain intermediate 2; S4, cool triethylenetriamine in an ice-water bath, pass nitrogen, slowly add intermediate 2 and methanol solution, react at 20-30°C for 2-5h, remove methanol under reduced pressure, raise the temperature to 130-160°C and continue to react under reduced pressure for 2-5h to obtain intermediate 3; S5, mixing the intermediate 3 and triphenyl phosphate, stirring evenly at 60-80° C. to obtain a modified epoxy resin; S6. Add modified epoxy resin and polyethyleneimine to the solvent in sequence, stir evenly, add the mixture into water and stir continuously for 10 to 30 minutes, add defoaming agent, stir evenly, seal and package to obtain a super hydrophilic flame retardant coating.

2. The super hydrophilic flame retardant coating containing nanomaterials according to claim 1, characterized in that: In the step S1, the mass ratio of ethanol, ammonia water, tetraethyl orthosilicate and γ-aminopropyltriethoxysilane is 100:5-10:5-10:0.5-2.

3. The super hydrophilic flame retardant coating containing nanomaterials according to claim 1, characterized in that: In the step S2, the mass ratio of bisphenol A epoxy resin to pyridine carboxylic acid is 1:0.4-0.

6.

4. The super hydrophilic flame retardant coating containing nanomaterials according to claim 1, characterized in that: In the step S3, the mass ratio of the intermediate 1, the amino-modified nano-silicon dioxide, and the catalyst concentrated sulfuric acid is 1:0.1-0.5:0.05-0.

1.

5. The super hydrophilic flame retardant coating containing nanomaterials according to claim 1, characterized in that: In the step S4, the mass ratio of triethylenetriamine, intermediate 2 and methanol solution is 1:1-1.5:2-3.

6. The super hydrophilic flame retardant coating containing nanomaterials according to claim 1, characterized in that: In the step S5, the mass ratio of the intermediate 3 to triphenyl phosphate is 1:0.3-0.

6.

7. The super hydrophilic flame retardant coating containing nanomaterials according to claim 1, characterized in that: The defoaming agent is polydimethylsiloxane.

8. The super hydrophilic flame retardant coating containing nanomaterials according to claim 1, characterized in that: The solvent is ethylene glycol, isopropanol or N,N-dimethylformamide.

9. An application of a super hydrophilic flame retardant coating containing nanomaterials as claimed in claim 1, characterized in that: The super hydrophilic flame retardant coating is used in construction engineering, road engineering, water conservancy engineering and medical industry.

10. The use of a super hydrophilic flame retardant coating containing nanomaterials according to claim 9, characterized in that: The preparation steps are as follows: The surface of the object to be coated is roughened and cleaned, placed in a dust-free room, dried at 60-80°C for 10-30 minutes, and the super-hydrophilic flame-retardant coating is evenly sprayed. After the spraying is completed, it is dried at 50-80°C for 5-10 minutes, and dried at a temperature of 200-400°C for 30-60 minutes. The coating on the surface of the object is completed.

Citation Information

Patent Citations

  • Hydrophilic flame-retardant modified polyimide fiber

    CN113773492A

Cited By

  • Fireproof anti-corrosion compression garbage truck metal box coating and preparation method thereof

    CN121379303A

  • Anti-cracking foaming composite coating for heat preservation of low-temperature cargo tank and preparation method of anti-cracking foaming composite coating

    CN122302672A

  • A low-temperature tank heat preservation anti-cracking foaming composite coating and a preparation method thereof

    CN122302672B